LC-Orbitrap-MS/MS Analysis of Chosen Glycation Products in Infant Formulas - Aleksandra Damasiewicz-Bodzek; Magdalena Szumska; Agnieszka Nowak; Sławomir Waligóra; Beata Pastuszka; Kamila Stopińska; Beata Janoszka (Molecules, 2025)
When breastfeeding is not possible, infant formulas may be used instead of human milk. However, harmful advanced glycation end-products (AGEs) may be formed during thermal processing of infant formulas. The exposure to AGEs at such an early age can lead to chronic diseases in the future. Therefore, the aim of this study was to develop a sensitive method to determine the content of AGEs in infant formulas. Twenty commercial infant formulas (initial and follow-on) in liquid and powder form were investigated using liquid chromatography with tandem mass spectrometry (LC-MS/MS) with a multistep sample pretreatment procedure. Five selected glycation products were analyzed: Nε-carboxyethyllysine (CEL), Nε-carboxymethyllysine (CML), furosine, glyoxal lysine dimer (GOLD), and methylglyoxal lysine dimer (MOLD). The mean contents of the tested glycation products did not differ significantly between the initial and follow-on formulas. No significant differences were found in the concentrations of the analyzed compounds from different manufacturers. However, the liquid formulas contained significantly more CML. The estimated dietary exposure to the tested compounds was in the range of 42.5–92.6 μg/day, except for furosine (almost 2 mg/day). The developed method enabled the determination of selected AGEs in complex matrices such as infant formulas. Consumption of liquid infant formulas can result in higher exposure to some AGEs.